Joyful witness in the Muslim world : sharing the gospel in everyday encounters - Reisacher, Evelyne A. (Grand Rapids, MI : Baker Academic, a division of Baker Publishing Group, 2016)
Joyful Witness in the Muslim World features global perspectives on current Christian engagement with Islam. It equips readers for mission among Muslims, exploring how to move from fear to joy in sharing the gospel. After emphasizing the importance of joy in the biblical narrative on mission and in human relationship building, Evelyne Reisacher surveys areas where Muslims and Christians encounter one another in the twenty-first century, highlighting innovative models of Christian witness in everyday life. Drawing on insights from global Christianity, this survey takes account of diverse conceptions of Muslim-Christian relations. It may surprise those who believe mission among Muslims is nearly impossible. Reisacher, who has decades of experience in engagement with Muslims, has noticed a certain dehumanization of Muslims by Christians. Muslims are seen as targets of mission instead of being accepted as human beings with whom we interact in everyday life. Walls have been erected between Muslims and Christians by social and political conflicts, and theological debates give the impression that Christians always meet with Muslims in extraordinary contexts. However, in today's global village, Muslims and Christians are likely to meet each other anywhere and everywhere. Reisacher demonstrates that suffering and joy in mission are not in contradiction. Joy can be a catalyst to relationship and witness in a world threatened by conflicts involving Christians and Muslims. This volume will help enhance global and local mission among Muslims. It will be of use to professors and students in mission courses, to mission training institutions and organizations, and to mission-minded pastors and mission committees in local churches. - From publisher.
Toward joyful witness -- Muslim-Christian attachment -- Connecting with iMuslims -- Joyful witness through art -- Thinking green in sharing the gospel -- Caring for the needy -- Meeting Muslim urbanites -- Theological conversations.
Includes bibliographical references and index.
Keywords: Missions to Muslims; Witness bearing (Christianity); Christianity and culture